Infringment of trademark right on ecommerce platforms: the performance of the platform and its impact on its liability - Antón Juárez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Electronic commerce platforms have become real main characters in the exchange of goods and services. Many of these platforms are mere intermediaries and only host information (hosting services). The role played by others, especially in recent years due to how digital services have changed, has led to the fact that it is not so easy to classify their activity and less include it within the consideration of “mere intermediaries”. Nevertheless, this is a key aspect when intellectual or industrial property rights are infringed on an ecommerce platform. In the present paper we are going to approach two analyzes. On the one hand, it is going to study when a platform uses a brand in the sense of EU Regulation 2017/1001, on the European Union trade mark. On the other hand, it will be analyzed when a platform, even if it does not use the brand, can be held responsible for the infractions that are being committed on its platform.
Keywords: trademark; ecommerce platform; civil liability